2022
DOI: 10.1177/09576509221109672
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance investigation of an axial flow compressor under water ingestion

Abstract: This paper presents numerical simulations of the effects of water ingestion in the axial flow compressor. A self-compiled droplet-wall interaction model is used to study the impingement of the droplets and the film fragmenting process on the surfaces of the compressor blades, which also included the splashing effects. The blade profile has been divided into small regions to effectively apply the rough wall model to capture the film-related flow losses, which has shown flow characteristics with better accuracy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Their results showed that cleaning efficiency is largely dependent on the jet velocity and the nozzle parameters used by the jet. Ishaque and Zheng [7] investigated the effect of incoming water on axial flow compressors through numerical simulations. A self-coded droplet-wall interaction model was used to study the droplet impingement and the film breaking process on the compressor blade surface, which also included the splash effect.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that cleaning efficiency is largely dependent on the jet velocity and the nozzle parameters used by the jet. Ishaque and Zheng [7] investigated the effect of incoming water on axial flow compressors through numerical simulations. A self-coded droplet-wall interaction model was used to study the droplet impingement and the film breaking process on the compressor blade surface, which also included the splash effect.…”
Section: Introductionmentioning
confidence: 99%